Techniques for success with implants in the esthetic zone - Happe, Arndt; Körner, Gerd ([S.l.] : Quintessence Publishing Co, Inc., 2019)
Implant restoration in the anterior region represents a particular challenge for dentists because even the most functional implant cannot be considered a success if the patient is still unhappy with their smile. Attention must be given to ensuring a high survival rate and a low complication rate, without sacrificing esthetics. In this book, the authors pass on their experience based on well-documented clinical cases and discuss all relevant aspects from the biologic basics and planning to surgery to prosthetic restoration in this challenging area. Modern microsurgical procedures for the augmentation of hard and soft tissue and plastic periodontal surgery are a special focus. Through numerous clinical photographs and schematic drawings, each procedure, whether simple or complex, is reproduced in comprehensive detail.
Techniques for success with implants in the esthetic zone -- Contents -- Foreword -- Preface -- Contributors -- 1. Introduction -- 2. Requirements -- 3. Microsurgery -- 4. Immediate Implant Placement in the Esthetic Zone -- 5. Implant Position, Planning, and Esthetic Analysis -- 6. Tooth Preservation Versus Extraction and Implant Placement -- 7. Adjacent Implants -- 8. Soft Tissue Augmentation -- 9. Bone Augmentation -- 10. Implant Exposure Techniques -- 11. Implant Abutments -- 12. Superstructure and Peri-Implant Restorative Interface -- 13. Complications -- 14. Complex Cases -- A-Z Index.
Includes bibliographical references and index.
Keywords: Dental Implantation; Esthetics, Dental